L'enjeu de la scolarisation en basque: différentiation selon les contextes sociolinguistiques et pratiques des élèves - Manterola, Ibon; Almgren, Margareta (My University, 2017)
This article analyses similarities and differences in oral language practices in a school activity in Basque and Spanish L1 and L2 respectively, in two groups of children from 5 to 11 years of age. These children proceed from different linguistic environments due to the sociolinguistic situation in the Basque Country. One of the groups has Basque as home language and is schooled in Basque with Spanish as a subject matter as from primary school. The other group, from Spanish-speaking families in a Spanish-speaking environment, is schooled in Basque in an early and total immersion programme, where Spanish is also introduced as a subject matter in primary education. The analysis shows similarities in the development in L1 and L2 in aspects such as narrative autonomy and the use of text organisers, but also differences in language specific features such as ergative case marking in Basque and the incorporations of lexical items from "the other language". The didactic gestures of the teachers aim at supporting the development of narrative skills in both languages.
Keywords: Basque; Espagnol; L1; L2; scolarisation en basque; pratiques narratives orales